Prevalence and factors associated with exclusive breastfeeding among rural mothers of infants less than six months of age in Southern Nations, Nationalities, Peoples (SNNP) and Tigray regions, Ethiopia: A cross-sectional study - Hagos, Dawit; Tadesse, Amare Worku (BMC, 2020)
Exclusive breastfeeding (EBF) is the global recommended nutrition for infants less than 6 months of age. The prevalence of exclusive breastfeeding in Ethiopia is much lower than the recommendations of World Health Organization (WHO). This study aimed to assess the prevalence and associated factors of EBF among rural mothers of infants less than 6 months of age in two regions, Southern Nations, Nationalities and Peoples (SNNP) and Tigray Regions, of Ethiopia. The research was based on the secondary data analysis of community-based cross-sectional study conducted in 56 rural woredas (districts) in two regions of Ethiopia for impact evaluation of Alive & Thrive multi-year project. The 24-h recall dietary data were collected from 600 mother-infant dyads where the infant was less than 6 month of age, using multistage cluster sampling technique and 584 dyads were found eligible for analysis. Bivariate and multivariable logistic regressions were applied to identify the associated factors of exclusive breastfeeding. The prevalence of EBF of infants less than 6 months of age was 88.0% (95% CI 84.9, 90.4%). The odds of practicing EBF were significantly higher among infants less than 2 months of age (AOR 4.47, 95% CI 2.41, 8.27), married mothers (AOR 4.35, 95% CI 1.50, 12.67), mothers who gave birth in health facilities (AOR 2.07, 95% CI 1.15, 3.73) and mothers who received breastfeeding counseling during pregnancy (AOR 2.23, 95% CI 1.26, 3.96). The prevalence of EBF was relatively high when compared with previous studies in Ethiopia but close to the WHO recommendations of 90 %. Infant age, marital status of mothers, delivery place and breastfeeding counseling during pregnancy were identified as factors associated with EBF practices in 24 h preceding the survey. Devising appropriate strategies on breastfeeding messaging/counseling and support in addressing poor breastfeeding practices through existing government-led health intervention packages are recommended.